Galectin-3 - an emerging prognostic indicator in advanced head and neck carcinoma - Plzák, Jan; Betka, Jan; Smetana, Karel; Chovanec, Martin; Kaltner, Herbert; André, Sabine; Kodet, Roman; Gabius, Hans-Joachim (European journal of cancer (Oxford, England, 2004)
Galectin-3, is a multifunctional effector. It is the only chimera-type member of the galectin family of endogenous lectins, which share specificity with beta-galactosides and have a jelly-roll-like folding pattern. It's activity profile includes modulation of cell-cell and cell-extracellular matrix interactions and the regulation of proliferation and apoptosis/anoikis. While lectin histochemistry with plant/invertebrate proteins is routine practice and immunohistochemical analysis of endogenous lectins has been thoroughly examined, the application of an endogenous lectin as a marker is presently primarily a promising concept. The aims of our study were to test galectin-3 as a technical probe and to correlate staining by the tissue lectin, localising accessible ligands in situ, to clinicopathological characteristics and the prognosis of patients (relapse-free and overall survival) in advanced head and neck squamous cell cancer. We measured galectin-3-dependent staining in 53 surgically resected oropharyngeal and laryngeal cancer specimens (stage III or IV). Patients were divided into two groups based on a threshold of 5% positivity in the tumour cell population. The patient's degree of positivity was significantly correlated with their level of differentiation and keratinisation and lack of lymph node involvement (P=0.0001, P=0.0007 and P=0.0224, respectively). Periods of relapse-free and overall survival were significantly shortened when the tumour population failed to meet the positivity criterion, i.e. to harbour ligands for the endogenous lectin (P=0.0039 and P=0.0259, respectively). We conclude that (a) studies with an endogenous lectin as a marker are technically feasible and (b) detection of accessible galectin-3-specific ligands is an independent prognostic marker in advanced head and neck squamous cell cancer with therapeutic potential. Of note, histochemical application of an endogenous effector after its purification and labelling may bear relevance beyond the galectins.
Keywords: galektin 3; Carcinoma, Squamous Cell; Female; ženské pohlaví; Immunohistochemistry; nádory hlavy a krku; lidé; Survival Analysis; následné studie; imunohistochemie; prognóza; Follow-Up Studies; Head and Neck Neoplasms; Galectin 3; Male; Aged; spinocelulární karcinom; Prognosis; analýza přežití; lidé středního věku; senioři; mužské pohlaví; Middle Aged; Humans